Discovery and Characterization of Diazenylaryl Sulfonic Acids as Inhibitors of Viral and Bacterial Neuraminidases - Hoffmann, Anja; Richter, Martina; von Grafenstein, Susanne; Walther, Elisabeth; Xu, Zhongli; Schumann, Lilia; Grienke, Ulrike; Mair, Christina E.; Kramer, Christian; Rollinger, Judith M.; Liedl, Klaus R.; Schmidtke, Michaela; et al. (Frontiers in Microbiology, 2017)
Viral neuraminidases are an established drug target to combat influenza. Severe complications observed in influenza patients are primarily caused by secondary infections with e.g. Streptococcus pneumoniae. These bacteria engage in a lethal synergism with influenza A viruses and also express neuraminidases. Therefore, inhibitors with dual activity on viral and bacterial neuraminidases are expected to be advantageous for the treatment of influenza infections. Here we report on the discovery and characterization of diazenylaryl sulfonic acids as dual inhibitors of viral and Streptococcus pneumoniae neuraminidase. The initial hit came from a virtual screening campaign for inhibitors of viral neuraminidases. For the most active compound, 7-[2-[4-[2-[4-[2-(2-hydroxy-3,6-disulfo-1-naphthalenyl)diazenyl]-2-methylphenyl]diazenyl]-2-methylphenyl]diazenyl]-1,3-naphthalenedisulfonic acid (NSC65847; 1), the Ki values measured in a fluorescence-based assay were lower than 1.5 µM for both viral and pneumococcal neuraminidases. The compound also inhibited N1 virus variants containing neuraminidase inhibitor resistance-conferring substitutions. Via enzyme kinetics and nonlinear regression modeling, 1 was suggested to impair the viral neuraminidases and pneumococcal neuraminidase with a mixed-type inhibition mode. Given its antiviral and antipneumococcal activity, 1 was identified as a starting point for the development of novel, dual-acting anti-infectives.